Numerical study of electro-convection between annular electrodes based on a dissociation-injection mechanism - Huang, Junyu (2024)
In this work, we extend the investigation of the injection-induced electro-convection (EC) between two-dimensional concentric electrodes from perfectly insulating dielectric liquids to dielectric liquids with residual conductivity. A dissociation-injection model of the EC system is implemented by a finite-volume framework of OpenFOAM®. The morphology of hetero-charge layers in a hydrostatic regime is presented. The flow characteristics including the spatial and temporal features of the flow field, electric field, and positive/negative charge density of the EC are analyzed. The subcritical bifurcation phenomenon of EC is observed. The residual conductivity postpones the onset of EC flow and inhibits the flow strength as EC takes place. The difference between onset (Tc) and cessation (Tf) of EC flow decreases as the residual conductivity grows. Gradually increasing the electric Rayleigh number (T), the EC system sequentially evolves via hydrostatic, steady, periodic, and chaotic states with abundant bifurcations. The initialization of the calculation could also strongly influence the instability of the EC system. Furthermore, the effect of residual conductivity on the transition sequences of the EC system is investigated. Four different transition sequences for EC develop from the hydrostatic state to chaos as T increases, and three distinct transition routes from the chaotic state to the motionless state when T reduces are observed and discussed.